1980
DOI: 10.1143/jjap.19.l109
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Behavior in the Copolymer of Vinylidenefluoride and Trifluoroethylene

Abstract: The linear and nonlinear dielectrical and depolarization processes of the copolymer of vinylidene fluoride and trifluoroethylene have been measured. The D vs. E hysteresis loop below room temperature indicates the ferroelectricity of this copolymer. The dielectric anomaly and the disappearance of remnant polarization at T0=70°C suggest that T0 is the phase transition temperature from the ferroelectricity to the paraelectricity phase. Results are analyzed on the basis of Weiss-type semimolecular theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
120
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(120 citation statements)
references
References 13 publications
0
120
0
Order By: Relevance
“…3 For PVDF, molecular modeling and experimental studies have identified several basic structures and conformations. 4 -7 The main intrachain vibrational modes range in frequency from about 400 to about 3000 cm Ϫ1 , while the interchain crystal vibrational modes are below 100 cm Ϫ1 .…”
Section: Introductionmentioning
confidence: 99%
“…3 For PVDF, molecular modeling and experimental studies have identified several basic structures and conformations. 4 -7 The main intrachain vibrational modes range in frequency from about 400 to about 3000 cm Ϫ1 , while the interchain crystal vibrational modes are below 100 cm Ϫ1 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the dependence of the coercive field, E., on the dipole density for the odd-numbered nylons. It is quite clear that the coercive fields for these four nylons increase successively, actually linearly, down the series, which indicates that it becomes more and more difficult for the polar amide groups to switch under the same applied electric field and the same experimental conditions, as the number of CH 2 groups decreases, while the number of hydrogen bonds per unit length of chain increases.…”
Section: Resultsmentioning
confidence: 95%
“…Poly(vinylidene fluoride) (PVF 2 )' and its copolymers 2 were the only known class of ferroelectric polymers until our discovery that melt-quenched and cold-drawn Nylon I 1 and Nylon 7 were also ferroelectric polymers exhibiting similar piezoelectric activity 3 ' 4 . Although large piezoelectric and pyroelectric coefficients have been measured on several polymer electrets such as amorphous poly(vinyl chloride)' and the amorphous copolymer of vinylidene cyanide-vinyl acetate 6 , it is commonly understood that in these amorphous systems field induced dipole orientation can be produced at temperatures equal to or greater than Ts, and "frozen in" by cooling under field.…”
Section: Introductionmentioning
confidence: 99%
“…Following wide angle x-ray diffraction studies and infrared absorbance measuremepts, two different dipole reorientation models based on 600 and 1800 rotations about the chain axis were proposed (4)(5)(6)(7). Hysteresis loops between the electric displacement D and the applied electric field E have been observed for phase I PVFZ using conventional ac techniques (8,9), and the switching times for polarization reversal have also been measured (10).…”
Section: Introductionmentioning
confidence: 99%